Service quality in the Singapore mobile phone industry after 1 April 2000 : the consumer's perspective. - Phua, Kevin Tshi Howe. (2008)
Provides a more customer-focused analysis of the service quality in the Singapore mobile phone industry after full liberalisation on April 1, 2000 using the SERVQUAL Model. Compares among the 3 market players: SingTel, M1 and StarHub; and attempts to highlight the possible actions likely to be taken by dissatisfied customers.